Analisis Risiko Produksi Bibit Sengon (Falcataria moluccana Miq.) Menggunakan Metode Fault Tree - Yodfiatfinda Yodfiatfinda; Fathiya Azzahra Putri; Rukavina Baksh (Jurnal Ilmu Kehutanan, 2023)
This research analyzed the sengon (Falcataria moluccana Miq.) seedling production risk and factors associated with the risks at the Research and Development Center for Forest Plant Seed Technology (BPPTPTH) Bogor. The data collection included interviews using questionnaires with 11 purposely selected respondents. This research employed the Fault Tree Analysis (FTA), a descriptive qualitative method, to analyze the seedling production risks. The results revealed two groups of risks, namely field and management production risks, that stemmed from eight primary roots. These eight primary roots included long seed storage time, far distance between the nursery and the researcher's office, lack of safety facilities, lack of employee skills, lack of employee appreciation, high frequency of employee absences for personal reasons, changes in seasons that cause changes in planting schedules, and changes in budget allocation. Inaddition to these eight main factors, leaf aphids and fungi attacks, including tumorrust(karat puru), could also increase seedling production risks.